2002
DOI: 10.1046/j.1460-9592.2002.00913.x
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of caudal ketamine, alfentanil and ketamine plus alfentanil administration for postoperative analgesia in children

Abstract: Caudal administration of ketamine 0.5 mg.kg-1 with or without alfentanil in children produced satisfactory postoperative analgesia without respiratory depression or other side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…11 DeNegri et al 12 showed that 0.5 mg/kg ketamine when added to caudal ropivacaine 0.2% provided better postoperative analgesia than clonidine without any clinically significant side effects in children undergoing minor surgery. Postoperative analgesia, as assessed by the Children's Hospital of Eastern Ontario Pain Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…11 DeNegri et al 12 showed that 0.5 mg/kg ketamine when added to caudal ropivacaine 0.2% provided better postoperative analgesia than clonidine without any clinically significant side effects in children undergoing minor surgery. Postoperative analgesia, as assessed by the Children's Hospital of Eastern Ontario Pain Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a strong difference between their study and ours in terms of the duration of analgesia; specifically, theirs had a longer duration than what was reported in our present study. The observed differences cannot be interpreted as superiority of results since they had used narcotics for caudal anaesthesia; the objective of using ketamine was to reduce the use of opioids so as to prevent the occurrence of respiratory complications [18]. Contrary to the results of our present study, Khan et al compared the effects of the use of a bupivacaine-tramadol combination and ketamine-bupivacaine combination, and reported that the first c ompound h ad a m uch b etter e ffect t han t he s econd c ompound, i n t erms o f controlling post-operative pain after inguinoscrotal surgery and having fewer side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although the given effect was dose-dependent, the best dosage of ketamine was equivalent to 0.5 mg/kg, and the use of higher doses was reported to cause problems and complications. Previously, Ozbek et al divided children admitted for the treatment of hypospadias into three groups, and administered alfentanil to the first group, ketamine to the second group, and a combination of the two drugs to the third group [18]. They then evaluated the duration of analgesia and pain intensity after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that caudal administration of ketamine 0.5 mcg/kg with or without alfentanil in children produced satisfactory postoperative analgesia without respiratory depression or other side-effects [98].…”
Section: Ketaminementioning
confidence: 98%